The Concepts of God and Power in the Subanon's Myth The Creation of the Earth and the First People - Biclar, Leo Andrew (JPAIR Multidisciplinary Research, 2015)
Literature is the bearer of the best treasures in the world. The values system of the Filipinos is embedded in their literature, in the same way that the Hebrew values system is anchored from the Old and New Testaments of the Bible. This literary criticism is descriptive-qualitative, employing the comparative and hermeneutical analyses of the Subanon's myth The Creation of the Earth and the First People and Hebrews beliefs on God's creation of the universe. It seeks to unfold the Filipino socio-cultural concepts of God shadowed through the characterization of the myth, analyze the politics of gender and power implicitly displayed by the characters, and draw out theoretical concepts from the analyses made. The findings concluded that the Subanon's myth nuances the peoples' beliefs on the creation of the universe, and entails to revive the familial values system of the Filipino, especially the love for children. The analysis unveils the gender roles of the Filipinos in the aboriginal period of history that have evolved to the development of gender equality in the present. Likewise, a theoretical concept of literary appreciation is developed through the established philosophy and background of the storyteller of an oral literature.
Keywords: Literary Criticism; Subanon myth; oral literature; descriptive-qualitative research; comparative analysis; Capiz; Philippines